Religious conversions in Singapore. - Lim, Lynette Jiaying. (2009)
Our project attempts to explore religious conversions in Singapore with respect to personal choice, socio-economic factors such as social mobility, education and family ties. Looking into the impact they have on their families and respective communities, the laws governing certain conversions and existing regional ties, the articles seek to provide an in-depth discussion on topic that is rarely mentioned in mainstream media.